Osteossíntese de fratura Salter-Harris tipo IV em cotovelo de cão da raça Pinscher - relato de caso - Rodrigues, Edinaldo Barros (Universidade Federal do Tocantins, 2024)
The Supervised Curricular Internship was carried out at the OLvet Veterinary Clinic in the areas of Small Animal Medical and Surgical Clinic, from August 14th to September 24th, 2023, under the supervision of Veterinary Doctor Rodolfo Olinto Rotoli Garcia de Oliveira. In total, the internship totaled 400 hours. During these periods, routine monitoring of the small animal medical clinic and small animal surgical clinic was carried out, enabling monitoring and participation in clinical, surgical, emergency and nursing care for patients. This report describes the events observed during the internship at this location, and presents an orthopedic case of osteosynthesis of a Salter Harris type IV fracture in the elbow of a Pinscher dog.Key-words: